2022
DOI: 10.1126/scitranslmed.abn7571
|View full text |Cite
|
Sign up to set email alerts
|

Triple-negative breast cancer metastasis involves complex epithelial-mesenchymal transition dynamics and requires vimentin

Abstract: Triple-negative breast cancer (TNBC) is an aggressive subtype associated with early metastatic recurrence and worse patient outcomes. TNBC tumors express molecular markers of the epithelial-mesenchymal transition (EMT), but its requirement during spontaneous TNBC metastasis in vivo remains incompletely understood. We demonstrated that spontaneous TNBC tumors from a genetically engineered mouse model (GEMM), multiple patient-derived xenografts, and archival patient samples exhibited large populations in vivo of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(61 citation statements)
references
References 82 publications
4
32
0
Order By: Relevance
“…A similar observation can be made on the epithelial-to-mesenchymal transition, whereas it constitutes a wide spectrum and cancer cells that present intermediary phenotype might be more metastatic (21)(22)(23). Some of those works have relied on the use of engineered experimental 3D models to investigate heterogeneity in a context of a heterogeneous population (21,22). Therefore, given the identified cell subpopulations, a logical next step would be to explore their actual contribution to BCa progression and resistance to therapeutics strategies in more advanced experimental models.…”
Section: Needs For Development Of New Research Modelssupporting
confidence: 60%
See 2 more Smart Citations
“…A similar observation can be made on the epithelial-to-mesenchymal transition, whereas it constitutes a wide spectrum and cancer cells that present intermediary phenotype might be more metastatic (21)(22)(23). Some of those works have relied on the use of engineered experimental 3D models to investigate heterogeneity in a context of a heterogeneous population (21,22). Therefore, given the identified cell subpopulations, a logical next step would be to explore their actual contribution to BCa progression and resistance to therapeutics strategies in more advanced experimental models.…”
Section: Needs For Development Of New Research Modelssupporting
confidence: 60%
“…Importantly, implication of EZH2 in tumor progression is not new and has been suggested in numerous tumor types from breast to prostate cancer and it can act as either as a tumor suppressor or as an oncogene (20). A similar observation can be made on the epithelial-to-mesenchymal transition, whereas it constitutes a wide spectrum and cancer cells that present intermediary phenotype might be more metastatic (21)(22)(23). Some of those works have relied on the use of engineered experimental 3D models to investigate heterogeneity in a context of a heterogeneous population (21,22).…”
Section: Needs For Development Of New Research Modelsmentioning
confidence: 94%
See 1 more Smart Citation
“…In addition, it is becoming more evident that cancer cell dissemination may not require complete EMT but rather fluid transitions between EM phenotypes or hybrid states, termed EM plasticity (EMP) (8 , 9, 10). Thus, it has been shown that E-cadherin expression can contribute to collective cell migration, establishment of metastases, chemotherapy resistance, and cancer cell survival under hypoxia (8,(11)(12)(13)(14)(15). Furthermore, a recent report confirmed that not only is E-cadherin expressed on cluster circulating tumor cells (cCTC), which are highly metastatic and predict poor outcome (16,17), but is even more abundant than EpCAM, the traditional epithelial marker for CTCs (18).…”
Section: Introductionmentioning
confidence: 99%
“…“These cancers often return within three years of diagnosis, and treatments used for other breast cancers do not typically work for triple‐negative [breast cancer],” said Andrew J. Ewald, PhD, the Virginia DeAcetis Professor in Basic Cancer Research, director of the Department of Cell Biology, and coleader of the Cancer Invasion and Metastases Program at the Sidney Kimmel Cancer Center at Johns Hopkins University School of Medicine, Baltimore, Maryland, in a news release accompanying a study published in Science Translational Medicine 1,2 …”
mentioning
confidence: 99%